Some Characteristics of Quality of Life and the Health of a Socially Prominent Male Buried at the Early Croatian Cemetery at Ždrijac in Nin (Archaeologia Adriatica, 2010)
The Eary Croatian cemetery at Ždrijac in Nin is rightfully considered one of the most important archaeological sites in Croatia. The systematic archaeological excavations of the cemetery began in 1969, under the direction of Prof. Dr. Janko Belošević, and continued to 1977. The cemetery is dated to the 8th and first half of the 9th century, and in terms of the archaeological finds and funerary architecture, it can be classified as a settlement cemetery organized in rows. Through study of the horizontal stratigraphy of the cemetery, it is possible to perceive individual groups of graves formed most probably on the basis of family relationships or clan membership. The most obvious example of such grouping can be found in the eastern part of the cemetery, where a certain number of graves was concentrated around grave 332, in which an Early Croatian high ranking family was buried. We received verbal confirmation from Prof. Dr. Janko Belošević that on the basis of the grave goods and the horizontal stratigraphy it is quite logical and justifiable to hypothesize that the individual from grave 312 (a well preserved skeleton of a man aged between 40 and 45) belonged to the same upper social class presumed for the family buried in grave 322. In this text we have compared the presence of various osteological (age, height, indicators of subadult stress, indicators of hard physical labor, and trauma analysis) and dental stress indicators (dental diseases that would indicate the type and quality of food) for the deceased individual from grave 312 with a sample composed of 22 individuals considered on the basis of the archaeological finds to belong to a lower social class. The aim was to establish whether the presence of the analyzed stress indicators correlated to a socially inferior status of the deceased. The results show that in the analyzed sample the above stress indicator were not correlated with social status, which suggests that the living conditions were relatively similar for all men at this Early Croatian site.
Keywords: Nin – Ždrijac; Early Croatian cemetery; osteological stress indicators; dental stress indicators; social status